Affective temperaments, self-schemas, and their interplay with emotional distress - Monsonet, Manel; Fagian-Núñez, Karen; Kwapil, Thomas R.; Barrantes-Vidal, Neus (Frontiers in Psychiatry, 2026)
BackgroundAffective temperaments and self-schemas are theorized to shape susceptibility to emotional distress, yet their interplay remains empirically unexplored. This study investigates (1) associations between affective temperaments and positive and negative self-schemas, and (2) whether positive and negative self-schemas mediate the temperament-distress relationship.MethodsA cross-sectional sample of 808 young adults (mean age = 20.8; 77.2% female) completed the TEMPS-A (affective temperaments), BCSS (self-schemas), and SCL-90-R (depressive/anxiety symptoms). Spearman correlations and parallel mediation analyses tested hypotheses.ResultsPositive self-schemas showed a positive association with hyperthymic temperament and inverse association with cyclothymic and depressive temperaments. Negative self-schemas were associated with cyclothymic and depressive temperaments and inversely associated with hyperthymic temperament. Mediation analyses revealed that both positive and negative self-schemas significantly mediated the relationships between cyclothymic, depressive, hyperthymic, and anxious temperaments with depressive symptoms. Conversely, positive self-schemas only mediated the pathway from hyperthymic temperament to anxiety symptoms, whereas negative self-schemas mediated all temperament-anxiety pathways.ConclusionThis study provides the first empirical evidence that self-schemas act as mediating mechanisms linking affective temperaments to affective symptoms. Our findings thereby support a biopsychosocial model of emotional distress, founded on the interaction between genetically-influenced temperaments and socially-constructed self-schemas. Consequently, therapeutic interventions designed to modify self-schemas may represent an effective strategy for mitigating the pathway from temperamental vulnerability to emotional distress.